Theorizing global studies - O'Byrne, Darren J. (Palgrave Macmillan, 2011)
"In recent years, a large number of theoretical models have been developed to try and make sense of today?s complex global society. This text identifies eight distinct models of global studies, such as Americanization, Homogenization, Balkanization and Creolization, enabling the reader to make sense of the full range of global issues and contending views on the existing world order. Within each module, present theoretical literature and key current issues are addressed with boxed case studies. Paying particular attention to human rights, the book provides students with the theoretical grounding and practical knowledge necessary for an understanding of globalization. This book explains the challenges and redefines the core theories of globalization. Using fascinating case studies to illustrate how each model works in practice, the chapters look at society, culture, politics and economics. This book gives students a solid understanding of current global conditions. Clear, concise and easy to read, this book explores key debates around global studies today. It examines the processes and dynamics of globalization that impact our modern world through clear explanation of complex theories. This book: - Presents 8 key models of global change - Brings together the ways in which sociology, politics and economics think about global studies - Covers a diverse range of major theorist in the field from Giddens to Huntington, and Wallerstein to Fukuyama - Brings to life contemporary issues, including the global financial crisis and the ware on terror Theorizing Global Studies is essential reading for all students of Sociology, Politics, International Relations and Global Studies"-- |c Provided by publisher.